2021
DOI: 10.3389/fphar.2021.643482
|View full text |Cite
|
Sign up to set email alerts
|

Palmul-Tang, a Korean Medicine, Promotes Bone Formation via BMP-2 Pathway in Osteoporosis

Abstract: Osteoporosis is a common skeletal disease in post-menopausal women. Palmul-tang, an herbal medicine, has been treated for gynecological disease such as anemia, anorexia, anti-fatigue, unspecified menstruation and female infertility in East Asia. In this study, ameliorative effects of Palmul-tang soft extracts (PMT), a Korean Medicine, on osteoporosis were investigated. Ovariectomized (OVX) osteoporotic ICR mice were intragastrically administrated PMT for 4 weeks. The level of bone mineral density (BMD) was ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Research indicated that monocropping was able to increase the proliferation and activity of ALP, bone matrix mineralization and the expression of bone matrix protein OPN accompanied by decreasing the production of IL-6 and IL-1b via suppressing the activity of the NF-kB signaling pathway (61). Choi et al (96) found that Palmultang could also increase bone mineral content and improve bone mineral density to treat OP. Furthermore, they indicated that the therapeutic effect of Palmul-tang mainly depended on up-regulating the expressions of BMP-2, Runx2, and Osx with its downstream factors ALP and OPN through the BMP-2 signaling pathway.…”
Section: Pharmaceutical Interventions Of Opn In Oa and Opmentioning
confidence: 99%
See 1 more Smart Citation
“…Research indicated that monocropping was able to increase the proliferation and activity of ALP, bone matrix mineralization and the expression of bone matrix protein OPN accompanied by decreasing the production of IL-6 and IL-1b via suppressing the activity of the NF-kB signaling pathway (61). Choi et al (96) found that Palmultang could also increase bone mineral content and improve bone mineral density to treat OP. Furthermore, they indicated that the therapeutic effect of Palmul-tang mainly depended on up-regulating the expressions of BMP-2, Runx2, and Osx with its downstream factors ALP and OPN through the BMP-2 signaling pathway.…”
Section: Pharmaceutical Interventions Of Opn In Oa and Opmentioning
confidence: 99%
“…Choi et al. ( 96 ) found that Palmul-tang could also increase bone mineral content and improve bone mineral density to treat OP. Furthermore, they indicated that the therapeutic effect of Palmul-tang mainly depended on up-regulating the expressions of BMP-2, Runx2, and Osx with its downstream factors ALP and OPN through the BMP-2 signaling pathway.…”
Section: Pharmaceutical Interventions Of Opn In Oa and Opmentioning
confidence: 99%
“…Many reports have suggested that RUNX2 is an important cytokine for early osteogenic differentiation [ 50 , 51 ]. On the one hand, RUNX2 can promote bone formation by influencing osteogenic differentiation indicators, such as ALP through its downstream gene OSX [ 52 , 53 ]. On the other hand, MMPs play a fundamental role in the process of mineralized matrix degradation that could lead to bone resorption, and the mechanism of their expression largely depends on the activation of osteogenic differentiation-specific transcription factors, such as RUNX2 [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we observed that the ALP enzyme increased the activity of early-differentiated cells and mature osteoblasts. It has been reported that herbal extracts such as Astragalus membranaceus, Palmul-tang, and Areca catechu increase ALP activity during early bone formation [19][20][21].…”
Section: Discussionmentioning
confidence: 99%